Career Guidance in High School to Reduce University Dropout in Madagascar - Rakotoniriana Noelisoa Jean Michel; Ralaivao Hanginiaina Emynorane; Razafitahindraza Erica Feyzine Sulla; Hangivola Emyblonde Ratna (Universitas Islam Negeri Mataram, 2026)
This study examines the role of career guidance in high school in reducing university dropout in Madagascar, with a focus on the Itasy region where students often face challenges in making informed academic and career decisions. The study aims to analyze how career guidance practices influence students’ readiness for higher education and their persistence in university. A qualitative approach was employed, involving 30 informants including high school students, teachers, school counselors, and university students. Data were collected through interviews, observation, and documentation, and analyzed using thematic analysis with triangulation to ensure credibility. The findings reveal that career guidance remains limited, irregular, and insufficiently integrated into school systems, leading to unclear career choices, low motivation, and difficulties in adapting to university studies. Social influences, particularly from families, also play a significant role in shaping students’ decisions, sometimes resulting in mismatches between interests and academic paths. The discussion emphasizes the importance of early, continuous, and context relevant career guidance to strengthen students’ self-awareness, adaptability, and decision-making skills. The study concludes that improving structured career guidance and fostering collaboration among schools, families, and communities can enhance students’ transitions to higher education and contribute to reducing university dropout in Madagascar.